2019
DOI: 10.1093/ecco-jcc/jjz164
|View full text |Cite
|
Sign up to set email alerts
|

Severe Attack of Henoch-Schönlein Purpura With Neurological Involvement During Adalimumab Treatment for Crohn’s Disease

Abstract: Tumour necrosis factor-α [TNF-α] inhibitors have revolutionised the management of chronic inflammatory conditions. A number of cutaneous adverse events have been reported with TNF inhibition, including vasculitis. Most reactions are mild and rarely warrant treatment withdrawal. Here we describe a patient with Crohn’s disease treated with adalimumab in whom severe multivisceral Henoch-Schönlein purpura developed, including neurological involvement, requiring definitive TNF blocker withdrawal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The four patients with atypical, prolonged courses of HSP were on anti‐TNF therapies, suggesting that anti‐TNF medications may play a role in triggering or prolonging IgA vasculitis in these patients. This hypothesis is supported by a recent review of 12 cases of new‐onset HSP in patients on anti‐TNF therapy, seven of whom had IBD 9 . Park et al 10 have previously suggested eosinophil activation in response to anti‐TNF agents as a possible pathogenic explanation for the development of HSP.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…The four patients with atypical, prolonged courses of HSP were on anti‐TNF therapies, suggesting that anti‐TNF medications may play a role in triggering or prolonging IgA vasculitis in these patients. This hypothesis is supported by a recent review of 12 cases of new‐onset HSP in patients on anti‐TNF therapy, seven of whom had IBD 9 . Park et al 10 have previously suggested eosinophil activation in response to anti‐TNF agents as a possible pathogenic explanation for the development of HSP.…”
Section: Discussionmentioning
confidence: 85%
“…This hypothesis is supported by a recent review of 12 cases of new-onset HSP in patients on anti-TNF therapy, seven of whom had IBD. 9 Park et al 10 have previously suggested eosinophil activation in response to anti-TNF agents as a possible pathogenic explanation for the development of HSP. Further studies are necessary to confirm this hypothesis and explore mechanisms for anti-TNF therapies in the pathogenesis of HSP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, biological agents, especially TNF-α blockers ( adalimumab , infliximab , etc.) are also commonly suspicious drugs, and case reports described the occurrence of IgAV with rare neurological involvement in Crohn’s patients after adalimumab treatment ( 131 ). Studies have suggested that TNF-α blockers can stimulate the formation of anti-tumor necrosis factor or tumor necrosis factor-containing immune complexes in small vessels and subsequently activating the complement pathway to induce vasculitis ( 132 ).…”
Section: Pathogenesismentioning
confidence: 99%